The Effect of Creativity and Product Innovation on Business Success in Coconut Shell Waste Craftsmen in The Bukit Lawang Plantation Village Bahorok District Langkat Regency - Elisa Fitri; Hesti Sabrina; Wan Rizca Amelia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2022)
This study aims to determine "The Effect of Creativity and Product Innovation on Business Success in Coconut Shell Waste Craftsmen in the Bukit Lawang Plantation Village, Bahorok District, Langkat Regency". This type of research is associative with a quantitative approach. The population in this study were 30 coconut shell craftsmen using the saturation point formula technique, because the population was less than 100 people, the number of samples in this study was taken absolutely from a population of 30 respondents. Based on the T test and F test, it can be concluded that the creativity and product innovation variables partially have a positive and significant effect on the success of the Coconut Shell Waste Craftsmen in the Bukit Lawang Plantation Village, indicating Ho is rejected and Ha is accepted. Coefficient of Determination (R2) = 0.343 or 34.3%. 65.7% was influenced by other factors not described in this study.